The long-term effects of parental marriage age on children’s educational human capital - Bohui Yuan; Yanping Pu (PLoS ONE, 2025)
This paper focuses on micro-level Chinese households and studies the impact of parental marriage age on the education outcomes of their children, utilizing data from the China Family Panel Studies (2020). Through OLS model regression, it is found that parents who get married later are better prepared to have children, marital stability is also stronger, and their children have a longer education period. But this positive effect will turn negative after the age of marriage exceeds 30. Further analysis reveals that parental age at marriage has a heterogeneous effect on their children’s educational attainment, which means mothers have a more significant impact on their children’s education outcomes than fathers.